Factors affecting the independence of tri guna karya group farmers in kintamani in processing and marketing their products - NI Ketut Karyati; Ni Nengah Yastini; Ni Wayan Suryathi; Anak Agung Ayu Rai Wahyuni (Institute for Advanced Science, Social, and Sustainable Future, 2023)
Indonesia As an agrarian country, agriculture are considered as one of the sectors that contributes to economic growth by providing essential needs such as food and even raw materials for industries. The agricultural sector is still capable of maintaining positive growth and finding ways to achieve the welfare and independence of farmers through empowerment processes. This is crucial as the majority of farmers in Indonesia are categorized as poor and marginalized. One initiative in this regard is the effort made by local governments to implement programs that strengthen business capital and empowerment programs to enhance farmers' self-sufficiency. This study aimed to identify and assess the factors that impact the self-sufficiency of farmers in the processing and marketing of agricultural products in Subak-Abian Tri Guna Karya, located in Kintamani District, Bangli Regency. The type of data used in this research is quantitative and qualitative data. Data collection techniques were carried out by conducting structured interviews, observation and documentation studies. The data analysis technique in this study is to use descriptive analysis techniques and statistical analysis. Based on the results of data analysis, Based on the findings of the research, it can be deduced that the factors affecting the self-sufficiency of farmers in the marketing and processing of agricultural products are evident in Subak-Abian Tri Guna Karya, Kintamani District, Bangli Regency are the individual characteristics of farmers who are characterized by skills, capacity strengthening factors that characterized by strengthening individual capacity, and development capital factors characterized by Human Resources (HR) capital, Quality human resource development is achieved by enhancing specific individual skills (life of skill) and strengthening individual capacity building to reinforce institutional development capacity building based on the Subak institution. This approach aims to enhance individual farmers' intellectual self-sufficiency.